In vivo visualization of the development of the enteric nervous system using a Tg(−8.3bphox2b:Kaede) transgenic zebrafish. Issue 12 (4th November 2014) - Harrison, Colin; Wabbersen, Tara; Shepherd, Iain T.
Summary The phox2b gene encodes a transcription factor that is expressed in the developing enteric nervous system (ENS). An enhancer element has been identified in the zebrafish phox2b locus that can drive tissue specific expression of reporter genes in enteric neuron precursor cells. We have generated a transgenic zebrafish line in which the Kaede fluorescent protein is under the control of this phox2b enhancer. This line has stable expression of the Kaede protein in enteric neuron precursor cells over three generations. To demonstrate the utility of this line we compared the migration and division rates of enteric neuron precursor cells in wild type and the zebrafish ENS mutant lessen. genesis 52:985–990, 2014. © 2014 Wiley Periodicals, Inc.